2020
DOI: 10.1139/as-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous participation in peer review publications and the editorial process: reflections from a workshop

Abstract: This communication paper reflects on discussions from a workshop about Indigenous involvement in the peer review and editorial processes. Arctic-based research is undergoing a paradigm shift to include local Indigenous peoples, their priorities, and knowledge throughout the research process. This special issue is an excellent example; it highlights research involving partnerships between Indigenous and non-Indigenous researchers to support knowledge co-production. Despite this shift, we find little space withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Another limitation of the evidence base is the inherent bias towards peer‐reviewed academic literature and underrepresents grey literature studies (from consultants or Indigenous organizations) or Indigenous‐led initiatives that were not documented through publications or reports. The associated bias for written material versus other mediums (e.g., video documentaries) and the unnecessary emphasis on Western peer‐review standards for credibility makes it difficult for non‐academic community reports or Indigenous‐led initiatives to bother going through the peer‐review process as Western practices of peer‐review do not align with Indigenous validation systems that are in place (see Loseto et al., 2020). Furthermore, some reports and studies may not be widely distributed or easily accessible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the evidence base is the inherent bias towards peer‐reviewed academic literature and underrepresents grey literature studies (from consultants or Indigenous organizations) or Indigenous‐led initiatives that were not documented through publications or reports. The associated bias for written material versus other mediums (e.g., video documentaries) and the unnecessary emphasis on Western peer‐review standards for credibility makes it difficult for non‐academic community reports or Indigenous‐led initiatives to bother going through the peer‐review process as Western practices of peer‐review do not align with Indigenous validation systems that are in place (see Loseto et al., 2020). Furthermore, some reports and studies may not be widely distributed or easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…It is equally important to note the limitations of the evidence base. Loseto et al, 2020). Furthermore, some reports and studies may not be widely distributed or easily accessible.…”
Section: Limitations Of the Evidence Basementioning
confidence: 99%
“…Recent work by Loseto et al has successfully addressed Indigenous involvement in peer review publications and the editorial process, in exploring the challenges of achieving equity in the research process. 34 Hence, some work is starting to challenge these issues at the broader level that marginalises Indigenous research. Further to this, guest editors for the A* Journal of Management have recently drawn on their experiences as a large network of racially diverse scholars and concluded that racial biases express themselves in differential responses, and they have attributed this to research topics and research samples.…”
Section: Constraints In Using Pacific Research Methodologies In Businessmentioning
confidence: 99%
“…The increased attention to Indigenous Knowledge and Indigenous participation in research and management is a major cultural shift in recent decades but is still in the early stages. More can and should be done (Pearce et al 2009;Loseto et al 2020). For authentic, meaningful collaboration and change, hunters and those impacted by the research and decisions need to be involved in all stages of a project or management system (Huntington 2021).…”
Section: Hudson Strait Pilot Project Outcomesmentioning
confidence: 99%